Fc-independent Phagocytosis: Implications for IVIG and other Therapies in Immune-mediated Thrombocytopenia - Li, June; E. van der Wal, Dianne; Zhu, Lingyan; Vadasz, Brian; K. Simpson, Elisa; Li, Conglei; Lee Webster, Michelle; Zhu, Guangheng; Lang, Sean; Chen, Pingguo; Zeng, Qingshu; Ni, Heyu (Cardiovascular & Haematological Disorders - Drug Targets, 2013)
Phagocytes were first described by Dr. Metchnikoff in 1873. The roles of phagocytes in innate and adaptive immunity have been well established to date, although the molecular mechanisms involved in initiating phagocytosis (through Fc or other receptors) remain to be further explored. Phagocytes in the reticuloendothelial system, particularly macrophages, have been implicated in the clearance of senescent blood cells. The destruction of these cells may be primarily mediated via an Fc-independent pathway. Fc-independent phagocytosis may also play an important role in platelet clearance, including in autoimmune thrombocytopenia (ITP), and in clearance of platelet-rich emboli detached from sites of vascular injury. In ITP, the two major platelet auto-antigens have been located on glycoprotein (GP)IIbIIIa and the GPIb complex. It has been demonstrated that anti-GPIb antibodies, in contrast to anti-GPIIbIIIa, can induce thrombocytopenia in an Fc-independent manner. We further demonstrated in an animal model that intravenous IgG (IVIG) is unable to ameliorate thrombocytopenia caused by most anti-GPIb antibodies, despite its efficacy in anti- GPIIbIIIa-mediated thrombocytopenia. Our data was supported by subsequent retrospective studies with ITP patients by several independent groups. Most recently, we found that anti-GPIb-mediated ITP was also resistant to steroid therapy and that platelet activation and apoptosis induced by anti-GPIb antibodies may be involved in the Fc-independent platelet clearance. Therefore, identification of antibody specificity in patients, e.g. anti-GPIIbIIIa (Fc-dependent) versus anti-GPIb (Fc-independent), may be important for therapies against ITP, as well as other immune-mediated thrombocytopenias.
Keywords: phagocytosis